(untitled) (Research, Society and Development, 2022)
The large volume of government data made available recently raises questions about the best way to display this data to the user. There is a direct relationship between most government portals called transparency portals, with a geographic region, whether this region is a city, state or country. User characteristics can influence the way they interact with applications, a way to soften this problem would be the use of information contextualization. It brings the user information based on their preferences, facilitating the interpretation and understanding of the data. For contextualization to occur, prior information is needed, which are usually collected through questions before the actual use, so that the application correctly filters the results. Therefore, this research proposed and developed new geovisualization metamodels and demonstrated their use by implementing them with adaptable resources according to the user’s profile. The choice of the model indicated for each profile considered the information obtained from the user, through the collection of responses in form format. Finally, the metamodels were written in library format and made available on the npm portal.